2021
DOI: 10.1039/d1cp01101d
|View full text |Cite
|
Sign up to set email alerts
|

The C(3P) + O2(3Σg) → CO2 ↔ CO(1Σ+) + O(1D)/O(3P) reaction: thermal and vibrational relaxation rates from 15 K to 20 000 K

Abstract: Thermal rates for the C(3P) + O2(3Σ-g) ↔ CO(1Σ+)+ O(1D)/O(3P) reaction are investigated over a wide temperature range based on quasi classical trajectory (QCT) simulations on 3-dimensional, reactive potential energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…Early emission spectra found that the C( 3 P) + O 2 ( 3 Σ g − ) reaction generates CO with v′ = 17 and that the transition state has the COO configuration rather than OCO. 43 As both the high-level CCSD(T)-F12 PES and a recently determined MRCISD+Q/aug-cc-pVTZ ground state PES 12 support stabilization of the COO structure, the present results also indicate that association of CO with O( 1 D) can lead to formation and stabilization of COO. Complementary to the O( 1 D) + CO( 1 Σ + ) reaction considered here, the O( 3 P) + CO( 1 Σ + ) process to yield triplet (excited) CO 2 is also feasible.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Early emission spectra found that the C( 3 P) + O 2 ( 3 Σ g − ) reaction generates CO with v′ = 17 and that the transition state has the COO configuration rather than OCO. 43 As both the high-level CCSD(T)-F12 PES and a recently determined MRCISD+Q/aug-cc-pVTZ ground state PES 12 support stabilization of the COO structure, the present results also indicate that association of CO with O( 1 D) can lead to formation and stabilization of COO. Complementary to the O( 1 D) + CO( 1 Σ + ) reaction considered here, the O( 3 P) + CO( 1 Σ + ) process to yield triplet (excited) CO 2 is also feasible.…”
supporting
confidence: 77%
“…9 Such a process has also been proposed to occur on interstellar grains 10 and has been confirmed experimentally 11 with an estimated entrance barrier of 0.014−0.103 eV for the process on ASW, compared with a value of 0.3 eV from high-level electronic structure calculations. 12 The surrounding water matrix provides the necessary coupling 8 to facilitate relaxation of the 3 A′ or 3 A″ states of CO 2 to the 1 A′ ground state (correlating with linear 1 Σ g + ). On the other hand, the presence of an entrance barrier for the O( 3 P) + CO( 1 Σ + ) reaction has one led to consider the alternative CO + OH pathway for CO 2 formation 13 which was, however, reconsidered to yield the HOCO intermediate in such environments in more recent experiments.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Noteworthy species like OH, CO, NH 3 , and CH 3 possess well-known VUV transitions, 47−50 although for some the intermediate state is strongly predissociative, and it remains to be seen how efficient and state-selective near-threshold multicolor REMPI schemes are best implemented for these species. Furthermore, making use of the recently reported near-threshold VUV-based REMPI schemes for H/D 51 or O( 3 P) atoms, 52 our approach provides a pathway to high-resolution and low-energy investigations of elementary reactive scattering processes that produce O or H atoms, such as C + O 2 → CO + O 35,53,54 or complex-forming reactions between Zeeman decelerated atoms and H 2 molecules. 55−57…”
mentioning
confidence: 99%